A pharmacist‐physician collaborative care model in chronic kidney disease. Issue 11 (26th October 2021) - Li, Hanlin; Radhakrishnan, Jai
Abstract: A multidisciplinary approach, including pharmacist interventions, has improved clinical outcomes and reduced economic costs in chronic disease management. To our knowledge, this is the first study to describe the incorporation of pharmacist‐driven medication management with partnering nephrologists while capitalizing on technology to improve outcomes in a Chronic kidney disease (CKD) population. The authors created a collaborative drug therapy management agreement to enhance medication management for hypertension and diabetes mellitus. Our metrics aligned with the Healthcare Effectiveness Data and Information Set (HEDIS) measures. Most referrals to the program met the HEDIS definition of suboptimal disease control (Diabetes: 19/25 and Hypertension: 45/70). In patients with multiple pharmacy visits, achievement of diabetes targets increased from 23% to 67% and hypertension from 29% to 58%. Those who used technology tools were more likely to reach goals. The positive impact of a pharmacist‐physician collaboration and utilization of technology tools present an opportunity to improve care for CKD patients.